2002
DOI: 10.1021/ja012750u
|View full text |Cite
|
Sign up to set email alerts
|

General Framework for Studying the Dynamics of Folded and Nonfolded Proteins by NMR Relaxation Spectroscopy and MD Simulation

Abstract: A general framework is presented for the interpretation of NMR relaxation data of proteins. The method, termed isotropic reorientational eigenmode dynamics (iRED), relies on a principal component analysis of the isotropically averaged covariance matrix of the lattice functions of the spin interactions responsible for spin relaxation. The covariance matrix, which is evaluated using a molecular dynamics (MD) simulation, is diagonalized yielding reorientational eigenmodes and amplitudes that reveal detailed infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
277
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(294 citation statements)
references
References 65 publications
15
277
0
2
Order By: Relevance
“…Such a procedure is a special case to the reporting of the dominant part of iRED eigenmodes together with their corresponding correlation times, from which the overall tumbling time can be modeled by fitting the correlation times of the five eigenmodes with the largest eigenvalues to the experimental data. 38 While in the present treatment isotropic overall tumbling is assumed, which is adequate for ubiquitin, 33 it can be easily extended to axially symmetric or fully anisotropic overall tumbling motion. 60 We find that for ubiquitin the modified AMBER99SB force field is better at reproducing both the amplitude and time scale of spin-relaxation active internal motions than AMBER99.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such a procedure is a special case to the reporting of the dominant part of iRED eigenmodes together with their corresponding correlation times, from which the overall tumbling time can be modeled by fitting the correlation times of the five eigenmodes with the largest eigenvalues to the experimental data. 38 While in the present treatment isotropic overall tumbling is assumed, which is adequate for ubiquitin, 33 it can be easily extended to axially symmetric or fully anisotropic overall tumbling motion. 60 We find that for ubiquitin the modified AMBER99SB force field is better at reproducing both the amplitude and time scale of spin-relaxation active internal motions than AMBER99.…”
Section: Discussionmentioning
confidence: 99%
“…Such advances would be particularly beneficial for assessing simulations of (partially) unfolded and disordered protein systems whose overall motion is not separable from internal dynamics and for which an internal order parameter is not defined any longer. 38,61,62 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Prompers and Brüschweiler combined molecular dynamics with NMR relaxation spectroscopy to study the dynamics of folded and unfolded proteins. 18 Zagrovic et al found that the mean structure averaged over unfolded ensemble of three different folds small proteins are nativelike. 19 Experimental information, such as NMR residual dipolar couplings, can be used as constraints to select unfolded state structures.…”
Section: Introductionmentioning
confidence: 99%